Dampak Perkawinan Yang Tidak Dicatat - Sarjiyati, Sarjiyati; Purwati, Yuni (Universitas Merdeka Madiun, 2019)
Marriage is a very important event in community life. Because marriage does not only concern the bride and groom, but also the parents of both parties, relatives and their families. The purpose of marriage is to form a happy and eternal family. The method used in this community service activity is legal counseling and discussion about not to noted marriages. From the discussion conducted it can be concluded that. The legal status of marriage that is not to noted under the marriage law is illegal or has no legal force. The legal status of a child born from a marriage that is not to noted has a civil relationship with his mother, this has the consequence that the child born of marriage is not to noted the country of the child does not have a civil relationship with his father. But after the decision of the Constitutional Court Number 46 / PUU-VIII / 2010 in which the child can also have a civil relationship with his father as long as it can be proven by technological tools such as DNA testing.